Exact boundary control for the wave equation in a polyhedral time-dependent domain - Bastos, W. D.; Ferreira, J. (Elsevier B.V., 1999)
We establish exact boundary controllability for the wave equation in a polyhedral domain where a part of the boundary moves slowly with constant speed in a small interval of time. The control on the moving part of the boundary is given by the conormal derivative associated with the wave operator while in the fixed part the control is of Neuman type. For initial state H-1 x L-2 we obtain controls in L-2. (C) 1999 Elsevier B.V. Ltd. All rights reserved.
Keywords: boundary controllability; wave equation